2021
DOI: 10.3390/ijms22168633
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Class IIa Histone Deacetylases Expression and In Vivo Epigenetic Imaging in a Transgenic Mouse Model of Alzheimer’s Disease

Abstract: Epigenetic regulation by histone deacetylase (HDAC) is associated with synaptic plasticity and memory formation, and its aberrant expression has been linked to cognitive disorders, including Alzheimer’s disease (AD). This study aimed to investigate the role of class IIa HDAC expression in AD and monitor it in vivo using a novel radiotracer, 6-(tri-fluoroacetamido)-1-hexanoicanilide ([18F]TFAHA). A human neural cell culture model with familial AD (FAD) mutations was established and used for in vitro assays. Pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 58 publications
2
12
0
Order By: Relevance
“…Chen and colleagues measured 11 C-PiB uptake in 5-, 8-and 11-month-old 3xTg-AD mice and age-matched controls, with a significant increase in uptake in the whole brain of transgenic mice at 5 and 8 months compared to WT [123]. However, a conflicting study found no significant differences between cerebral 11 C-PiB uptake in 4-, 8-, 12-, and 16-month-old transgenic and WT male mice.…”
Section: Pet: Amyloid Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Chen and colleagues measured 11 C-PiB uptake in 5-, 8-and 11-month-old 3xTg-AD mice and age-matched controls, with a significant increase in uptake in the whole brain of transgenic mice at 5 and 8 months compared to WT [123]. However, a conflicting study found no significant differences between cerebral 11 C-PiB uptake in 4-, 8-, 12-, and 16-month-old transgenic and WT male mice.…”
Section: Pet: Amyloid Imagingmentioning
confidence: 99%
“…Class IIa histone deacetylase (HDAC) PET imaging was also tested by Chen, using the HDAC4 and HDAC5 tracer 18 F-TFAHA. The results show that the uptake in the whole brain of 8- and 11-month-old transgenic mice was 1.15- and 1.63-fold higher than in the WT, respectively [ 123 ]. The 11-month-old transgenic mice showed an almost 2-fold (significant) increase in 18 F-TFAHA uptake in the striatum, cortex, hippocampus, basal forebrain, thalamus, hypothalamus, amygdala, and cerebellum relative to WT.…”
Section: Neuroimaging Of Mouse Models Of Admentioning
confidence: 99%
See 1 more Smart Citation
“…[89] SV2A [ 11 C]UCB-J Striatal-lesioned rats [14,103,104] APP/PS1 mice [104] ArcSwe, Tg-L61 mice [105] [ 18 F]SynVesT-1 APP/PS1 mice [107] mGluR5 [ 18 F]FPEB 5×FAD mice [131,277] APP/PS1 mice [132] [ 11 C]ABP688 Tg-ArcSwe mice [133] 7nAChR IIa HDAC [ 18 F]TFAHA 3×Tg mice [278] GLP-1R [ 18 [ 11 C]tariquidar APP/PS1 mice [166] P-GP ABCB1…”
Section: Fundingmentioning
confidence: 99%
“…Recently, HDAC inhibitors have been established in patients with AD as potential targets due to their wide scope of effects, ranging from decreased deposition of Amyloid β-peptides, an immune response triggered by microglia, reduced β-secretase cleavage, regulated levels of SIRT1, BDNF, ABCA7, REST, LTP deficits and decreased phosphorylation and acetylation of Tau ( Wang et al, 2019a ; Rusek et al, 2019 ). Moreover, deacetylase classes of HDAC4 and HDAC2 levels were significantly upregulated in areas of the hippocampus, prefrontal cortex, and the basal forebrain region of neuronal cultured cells, in AD mouse models, ( Chen et al, 2021 ). In the CK-p25 AD mouse model, increased binding of HDAC2 to promoter regions of genes with critical roles in learning and memory and synaptic plasticity was accompanied by reduced acetylation levels of H2BK5, H3K14, H4K5, andsq1 H4K12, reduced RNA polymerase II binding, and reduced gene expression ( Giusti-Rodríguez et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%